2022
DOI: 10.3390/environments9070075
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study to Quantify Volatile Organic Compounds and Their Sources Inside and Outside Homes in Urban India in Summer and Winter during Normal Daily Activities

Abstract: Indian cities have some of the poorest air quality globally but volatile organic compounds (VOCs)—many of which adversely affect health—and their indoor sources remain understudied in India. In this pilot study we quantified hundreds of VOCs inside and outside 26 homes in Ahmedabad and Gandhinagar, Gujarat, in May 2019 and in January 2020. We sampled in the morning and afternoon/evening to capture temporal variability. Total indoor VOCs were measured at higher concentrations in winter (327.0 ± 224.2 µgm−3) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Ethylene concentrations at the forested P2 point showed a smaller decrease. The results suggest a strong seasonal dependence, with changes in pollutant concentrations during the day potentially attributed to photochemical reactions of VOCs, fluctuations in temperature and humidity, and pollutant emissions resulting from human activities [55]. F. Meneguzzo et al conducted an investigation using a photoionization detector to analyze the concentrations of total VOCs in various environments in the Italian northern Apennines [56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethylene concentrations at the forested P2 point showed a smaller decrease. The results suggest a strong seasonal dependence, with changes in pollutant concentrations during the day potentially attributed to photochemical reactions of VOCs, fluctuations in temperature and humidity, and pollutant emissions resulting from human activities [55]. F. Meneguzzo et al conducted an investigation using a photoionization detector to analyze the concentrations of total VOCs in various environments in the Italian northern Apennines [56].…”
Section: Discussionmentioning
confidence: 99%
“…F. Meneguzzo et al conducted an investigation using a photoionization detector to analyze the concentrations of total VOCs in various environments in the Italian northern Apennines [56]. Their findings revealed a peak in VOC concentrations in the early morning and the lowest concentrations in the late afternoon on clear and calm days [55,56]. The study also demonstrated that ethylene, benzene, and toluene exhibited morning peaks (8:30-11:30 a.m.) with decreasing levels in the evening (5:30-8:30 p.m.), as depicted in Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…55 In contrast to IAP studies in developed countries, IAP measurements in India are limited in parameters, duration, spatial locations, and nature of measurements (offline and online). Some IAP studies conducted in India are listed in 29,44 While these species are important, other species, such as O 3 , speciated organics, and chlorinated species, are yet to be measured extensively in urban-Indian built environments. The omission of these gaseous species hinders the understanding of indoor physicochemistry and the full scope of health impacts of IAP.…”
Section: Status Of Iaq Measurement Studies In Indiamentioning
confidence: 99%
“…Datta et al also included real-time VOC measurements without any further chemical speciation . Offline gaseous measurements included Cl 2 , H 2 S, NH 3 , polycyclic aromatic hydrocarbon (PAH), CS 2 , and chemically speciated VOCs. , While these species are important, other species, such as O 3 , speciated organics, and chlorinated species, are yet to be measured extensively in urban-Indian built environments. The omission of these gaseous species hinders the understanding of indoor physicochemistry and the full scope of health impacts of IAP.…”
Section: Status Of Iaq Measurement Studies In Indiamentioning
confidence: 99%
“…The resulting indoor pollutants have been identified as PM, noxious gases, bacteria, fungi, insects, etc. [25][26][27]. The major indoor toxic gases involve the oxides of carbon (COx) (carbon monoxide (CO) and carbon dioxide (CO 2 )) [28], oxides of nitrogen (NOx) (nitric oxide (NO) and nitrogen dioxide (NO 2 )) [29,30], oxides of sulfur (SOx) (sulfur dioxide (SO 2 )) [31], PM [32][33][34], radon [35,36], volatile organic matter (VOC) [37], carbonaceous aerosols/biological aerosols/microorganisms (bacteria, viruses, fungi) [38][39][40], and pesticides [41].…”
Section: Indoor Air Pollutionmentioning
confidence: 99%